Why small-quantity lipid-based nutrient supplements should be integrated into comprehensive strategies to prevent child undernutrition in nutritionally vulnerable populations: response to Gupta et al.’s commentary - Dewey, Kathryn G.; Stewart, Christine P.; McDonald, Christine M.; Wessells, K. Ryan; Arnold, Charles D.; Prado, Elizabeth L.; Abbeddou, Souheila; Adu-Afarwuah, Seth; Arnold, Benjamin F.; Ashorn, Per; Ashorn, Ulla; Ashraf, Sania; et al. (World Public Health Nutrition Association, 2023)
We write in response to the commentary by Gupta et al. (2023) on small-quantity lipid-based nutrient supplements (SQ-LNS) for infants and young children 6 to 24 months of age, which was prompted by the recent brief guidance note from UNICEF (2023) explaining when, why and how SQ-LNS are being prioritized as part of their package of preventive actions to combat early childhood malnutrition. The UNICEF document was disseminated shortly after publication of a correspondence in Nature Food (Aguayo et al. 2023), authored by nutrition leaders from several organizations, that summarized the evidence on the benefits of SQ-LNS and called for this intervention to be scaled up and integrated into programs for populations in which child undernutrition is prevalent and dietary quality is very poor.